PLASMA-ASSISTED EXTRACTION OF COMMON NETTLE BY-PRODUCTS - Bogdanović, Mihajlo; Mladenović, Dragana; Grbić, Jovana; Lazović, Saša; Djukić-Vuković, Aleksandra (Journal on Processing and Energy in Agriculture, 2024)
Nettle (Urtica dioica) is a wild plant rich in flavonoids, carotenoids, phytosterols, and terpenes. It has exceptional pharmaceutical potential due to its anti-inflammatory, antioxidant, and diuretic properties. It is used in food, as tea, or in the form of dry or liquid extracts. To improve the characteristics, bioavailability, and stability of extracts, extractions with environmentally acceptable solvents, green physical treatments, and fermentation with probiotic bacteria are used. Green solvents such as water, ethanol, and biocompatible eutectic liquids are suitable for obtaining extracts following the principles of sustainable development. Innovative physical treatments such as non-thermal plasma treatment can ensure better extraction and microbiological stability, especially of aqueous extracts. Also, bacterial fermentations, such as Ligilactobacillus salivarius, can metabolize the compounds present in the extracts and biotransform glycosides, tannin, and lignan into biologically active forms. In this paper, we examined the growth and antioxidant activity of aqueous extracts of nettle flowers obtained with non-thermal plasma treatment and subsequent fermentation with L. salivarius. A positive combined effect of non-thermal plasma and fermentation on increasing antioxidant activity was observed, especially during shorter treatments with non-thermal plasma. The results of the work indicate the possibility of applying green treatments and fermentation to obtain nettle flower extract products enriched with L. salivarius. Plasma treatment can also be used on the microbiological composition of water extracts, as an important aspect for application in the food and pharmaceutical industry.
Keywords: common nettle; antioxidant activity; Ligilactobacillus salivarius; non-termal plasma